2024
DOI: 10.3390/ijms25116100
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Autophagy and Apoptosis of Fibrosarcoma HT-1080 Cells Mediated by Chalcone with Indole Moiety

Ewelina Honkisz-Orzechowska,
Olga Barczyk-Woźnicka,
Maria Kaleta
et al.

Abstract: This study demonstrated the anticancer efficacy of chalcones with indole moiety (MIPP, MOMIPP) in fibrosarcoma cells for the first time. The results showed that MIPP and MOMIPP reduced the viability of HT-1080 cells in a concentration-dependent manner. MOMIPP was more active than MIPP in HT-1080 cells, showing lower IC50 values (3.67 vs. 29.90 μM). Both compounds at a concentration of 1 μM induced apoptosis in HT-1080 cells, causing death strictly related to caspase activation, as cell viability was restored w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…On the other hand, it has been reported that a series of synthetic chalcones (indolyl-pyridinyl-propenones; IPP) induce non-apoptotic cell death. Honkisz-Orzechowska et al investigated the effect of the most active compounds, MIPP (3-(2-Methyl-1-H-indol-3-yl)-1-(4-pyridinyl)-2-propen-1-one) and MOMIPP (3-(5-methoxy-2-methyl-1H-indol-3-yl)-1-(4-pyridinyl)-2-propen-1-one) on HT-1080 fibrosarcoma cells [ 5 ]. In their study, MIPP and MOMIPP dose-dependently inhibited the viability of HT1080 cells.…”
mentioning
confidence: 99%
“…On the other hand, it has been reported that a series of synthetic chalcones (indolyl-pyridinyl-propenones; IPP) induce non-apoptotic cell death. Honkisz-Orzechowska et al investigated the effect of the most active compounds, MIPP (3-(2-Methyl-1-H-indol-3-yl)-1-(4-pyridinyl)-2-propen-1-one) and MOMIPP (3-(5-methoxy-2-methyl-1H-indol-3-yl)-1-(4-pyridinyl)-2-propen-1-one) on HT-1080 fibrosarcoma cells [ 5 ]. In their study, MIPP and MOMIPP dose-dependently inhibited the viability of HT1080 cells.…”
mentioning
confidence: 99%